HUBUNGAN HIPERTENSI DENGAN KADAR KOLESTEROL LDL PADA PASIEN SINDROM KORONER AKUT DI RUMAH SAKIT UMUM SANTO ANTONIUS PONTIANAK TAHUN 2019-2021 - Christin Angelia; Andria Priyana (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2023)
High blood pressure (hypertension) is a non-communicable disease that can cause death and many complications, especially complications related to the cardiovascular system. According to data from the Indonesian Basic Health Research (Riskesdas) in 2018, the prevalence of hypertension in Indonesia was 8.36%. Hypertension is a controllable risk factor for acute coronary syndrome. One of the causes of hypertension is rarely doing physical activity so that it can increase cholesterol levels in the body which can cause cardiovascular-related diseases. This study aims to determine the relationship between hypertension and LDL cholesterol levels at Rumah Sakit Umum Santo Antonius Pontianak. This research is an observational analytic study with a cross-sectional design. The sampling was carried out by convenience sampling to obtain a sample of 776 respondents. Data collection was collected using secondary data, medical records on LDL cholesterol levels and blood pressure to determine whether or not they have hypertension in acute coronary syndrome patients. The results of Chi-square analysis showed that there was a significant relationship between LDL cholesterol levels and hypertension (p-value 0.05) and epidemiologically, it was found that patients with Acute Coronary Syndrome who have abnormal LDL cholesterol have a 1.681 times risk of experiencing high blood pressure (hypertension). The conclusion of this study is that  abnormal LDL cholesterol level can affect a person's blood pressure which later if not treated immediately will experience acute coronary syndrome